Nanotecnologia aplicada ao sistema cardiovascular: efeito do fulerol no estresse oxidativo - Marina de Souza Ladeira (2013)
The oxidative stress related to enhanced concentration of reactive oxygen species (ROS) is associated to the progression of cardiovascular dysfunction. In the heart, the oxidative stress can affect the structure and function of the myocardium, resulting in hypertrophy and apoptosis of the myocytes. Beyond the effects on the heart, the oxidative stress is associated to endothelial dysfunction, affecting the vascular tonus. Therefore, treatments with antioxidants present therapeutic potential and may attenuate the cardiovascular dysfunction and prevent the progression of heart failure. Among the antioxidants, fullerol has gained much attention due to its ability to complex to ROS and therefore, inhibiting the oxidative damage. Fullerol is a spherical carbon nanostructure known as a powerful antioxidant due to its reactivity to electron rich species, as the major molecular structure with pi ligands per volume. The present study aimed to evaluate the effects of fullerol oncardiovascular dysfunction induced by oxidative stress. Our in vitro assay showed the protect effects of fullerol on the molecular and biochemical alterations induced by isoproterenol and phenylephrine treatment inneonatal cardiomyocytes isolated from Wistar rats. Fullerol administration prevented the enhancement of ROS production, the increase in cellular area and expression of proteins that are involved in the hypertrophic signaling (calcineurin and NFAT) induced by adrenergic agonist treatment in cardiomyocytes. We observed, in vivo, that concomitant treatment with fullerol in male Wistar rats was able to reducelipoperoxidation induced by isoproterenol, contributing to the improvement of the cardiac function and calcium handling, attenuating the development of fibrosis and hypertrophy of ventricular myocytes. Moreover, we evaluated the effects of fullerol on the endothelial dysfunction induced by paraquat exposure in the isolated aorta of Wistar rats and in the aorta of apoE knockout (KO) mice. We observed that fullerol incubation restored vascular reactivity preventing the endothelial dysfunction, characterized by a reduction of the relaxation induced by acetylcholine on vessels exposed to paraquat or from apoE KO animals.Therefore, we can conclude that, fullerol has antioxidant activity capable ofpreventing the deleterious effects of oxidative stress on the cardiovascular system.